2018
DOI: 10.1136/bmjopen-2017-021367
|View full text |Cite
|
Sign up to set email alerts
|

Obstacles to diagnosis and treatment of Lyme disease in the USA: a qualitative study

Abstract: ObjectiveFor many individuals with Lyme disease, prompt treatment leads to rapid resolution of infection. However, severe complications can occur if treatment is delayed. Our objective was to identify themes around belated diagnosis or treatment of Lyme disease using the General Model of Total Patient Delay (GMTPD).DesignWe conducted a qualitative interview study using indepth telephone interviews.SettingParticipants were patients from a large, integrated health system in the state of Pennsylvania, USA.Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
(18 reference statements)
3
30
0
Order By: Relevance
“…While delayed diagnosis appears to be common in those with chronic Lyme disease, the extent of the problem for the full disease spectrum is unknown. However, some researchers suggest that delayed diagnosis may occur in as many as 40% of cases [3].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While delayed diagnosis appears to be common in those with chronic Lyme disease, the extent of the problem for the full disease spectrum is unknown. However, some researchers suggest that delayed diagnosis may occur in as many as 40% of cases [3].…”
Section: Resultsmentioning
confidence: 99%
“…The Centers for Disease Control and Prevention (CDC) estimates that 300,000 new cases of Lyme disease occur annually [1]. Although most patients who are diagnosed and treated early are restored to health, treatment failures ranging from 10% to 35% have been reported, and many patients are not diagnosed until later in the disease when treatment success is much harder to achieve [2,3,4,5,6,7,8,9]. Compared to other diseases, very little research has been conducted on how best to treat patients who do not respond to short-term treatment approaches [10].…”
Section: Introductionmentioning
confidence: 99%
“…One recent study has shown that the presence of pre-existing co-morbidities in Lyme disease was predictive of long-term symptoms and lower quality of life (39), similar to other disease settings (40,41). Delays in diagnosis and initiation of appropriate treatment, which importantly may be driven by patient health insurance status (42), have also been shown to increase risk (31,32). Diagnostic delays may also be compounded in some initially misdiagnosed patients by subsequent exposure to inappropriate or ineffective treatments (15,43).…”
Section: Risk Factorsmentioning
confidence: 95%
“…While it is unknown whether corticosteroid exposure during acute infection, often prescribed for associated facial palsies, may affect resolution of systemic symptoms, it has been shown to be associated with worse long-term facial function outcomes (44,45). Although awareness of Lyme disease has increased in recent decades, the wide range of clinical heterogeneity at presentation and the limited sensitivity of the two-tier test mean that misdiagnosis and delays in diagnosis still occur with some frequency in the community practice of medicine (42,43).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation